Influence of Karst Caves on the Pile’s Bearing Characteristics-A Numerical Study - Liang, Jia-hui; Fan, Qiu-yan; Qin, Kuo (Frontiers in Earth Science, 2022)
Compared with the amount of research undertaken on vertical-bearing piles in karst areas, there are fewer studies on the stability of horizontal-bearing piles (e.g., anti-slide piles and supporting piles), and little in the way of theoretical developments. In order to study the influence of karst cave in front of and under the pile on the stability of anti slide pile, this study designs orthogonal test, carries out numerical simulation by using ABAQUS finite element analysis software, deduces the displacement load curve of each group of piles, and then determines the lateral ultimate bearing capacity of anti slide pile when karst cave exists, and Through multiple linear regression analysis and test on the parameters such as the distance between the karst cave under the pile and the pile tip, the span height ratio of the cave in front of the pile and the span height ratio of the cave under the pile, it is concluded that there is a significant correlation between the above participation and the lateral ultimate bearing capacity. The research results have certain guiding significance for the application of anti slide pile in karst area.